A BRIEF OVERVIEW OF THE KOREAN NATIONAL ASSEMBLY - Ж.ТӨРТОГТОХ (Politology, 2023)
In this paper, the author considers the Republic of Korea’s legislative institution. In order to develop the parliamentary institution in the present social conditions of Mongolia, it is required to identify and describe the Parliament’s operation, functions, features, and its status in the state structure and conduct comparative study of the Parliament of Republic of Korea. In connection with the above, it is essential to emphasize theoretical and practical issues related to features of functions, electoral mechanisms, operation and status of the Republic of Korea’s parliament in the political system.